Mechanosensing of cells in 3D gel matrices based on natural and synthetic materials. (27th August 2014) - Shan, Jieling; Chi, Qingjia; Wang, Hongbing; Huang, Qiping; Yang, Li; Yu, Guanglei; Zou, Xiaobing
Abstract Cells in vivo typically are found in 3D matrices, the mechanical stiffness of which is important to the cell and tissue‐scale biological processes. Although it is well characterized that as to how cells sense matrix stiffness in 2D substrates, the scenario in 3D matrices needs to be explored. Thus, materials that can mimic native 3D environments and possess wide, physiologically relevant elasticity are highly desirable. Natural polymer‐based materials and synthetic hydrogels could provide an better 3D platforms to investigate the mechano‐response of cells with stiffness comparable to their native environments. However, the limited stiffness range together with interdependence of matrix stiffness and adhesive ligand density are inherent in many kinds of materials, and hinder efforts to demonstrate the true effects contributed by matrix stiffness. These problems have been addressed by the recently emerging exquisitely designed materials based on native matrix components, designer matrices, and synthetic polymers. In this review, a variety of materials with a wide stiffness range that mimic the mechanical environment of native 3D matrices and the independent affection of stiffness for cellular behavior and tissue‐level processes are discussed.